A light-cured ceramic core powder grading design method and a core preparation method

CN122987192APending Publication Date: 2026-10-27SHANGHAI JIAOTONG UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202610868558.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-16
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0005]通过粉料的级配可以提升陶瓷型芯的力学性能,但是如何在陶瓷浆料阶段通过最佳颗粒配比进行级配,实现粉末紧密堆积、高性能、尺寸精度良好且无裂纹的陶瓷型芯材料缺乏较好的设计方法,通常是通过不断调整颗粒配比进行级配调整,试错成本高,效率低下

Benefits of technology

1、通过本发明的设计方法,可以基于最佳颗粒匹配模型指导陶瓷粉末的不同颗粒大小级配,降低试错成本,实现高效材料迭代,极大缩短了先进复杂结构陶瓷型芯结构的迭代周期,缩短先进航空发动机验证周期,降低涡轮叶片结构的研发成本和批量制备成本,有利于智能制造绿色化,降低能耗。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122987192A_ABST
    Figure CN122987192A_ABST
Patent Text Reader

Abstract

The application relates to a photocuring ceramic core powder grading design method and a core preparation method, which comprises the following steps: obtaining the particle size distribution of ceramic powder to be graded for particle size distribution testing; calculating the total porosity epsilon of the system containing different particle size ceramic powders through a Horsfield model; calculating the system bulk density, the total surface energy E of the system and the viscosity eta of the ceramic suspension slurry containing different particle size ceramic powders; outputting the optimal ceramic powder grading model according to the weight method by minimizing the total surface energy of the system and the viscosity of the ceramic suspension slurry and maximizing the system bulk density; calculating the particle size ratio of each ceramic powder according to the process setting constraints; preparing ceramic slurry according to the obtained particle size ratio of the ceramic powder, making a ceramic core sample; and performing performance testing and analysis on the ceramic core sample. Through the application, the optimal particle matching model can be used to guide the grading of different particle sizes of the ceramic powder, the trial and error cost is reduced, efficient material iteration is realized, and the iteration cycle is greatly shortened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of investment casting for aero-engine blades, specifically to a method for designing the powder gradation of photocurable ceramic cores and a method for preparing the cores. This method is suitable for high-precision, moldless, small-batch preparation of silicon-based ceramic cores for advanced aero-engine turbine blades, in order to meet the high-frequency iterative verification requirements of turbine blade structural design. Background Technology

[0002] As a key auxiliary material for the precision casting of turbine blades for aero-engines, the complex structure of ceramic cores largely determines the dimensional accuracy, yield rate, and manufacturing cost of the blades. Traditional mold-forming methods for ceramic cores, with increasingly complex structures, require multiple sets of molds to meet precision requirements, resulting in high development costs and long cycles, failing to meet the demands for rapid iteration of ceramic core structures. In contrast, photopolymerization additive manufacturing technology enables moldless forming and reduces processes, accelerating the iteration cycle of ceramic core structures and providing a new manufacturing technology for producing ceramic cores for high thrust-to-weight ratio turbine blades.

[0003] Although photopolymer additive manufacturing technology can achieve rapid moldless molding of ceramic cores, it faces challenges such as cracks, large dimensional deformation, and insufficient mechanical and thermal properties after the ceramic cores are sintered.

[0004] Existing technologies, such as patent document CN114853450A, disclose a method for preparing photopolymerizable 3D printed alumina-based ceramic cores. This method proposes a graded mixture of coarse, medium, and fine alumina ceramic powders, modified with a surface modifier, and then mixed with a photosensitive resin mixture via ball milling to obtain a high-solids-content, graded photopolymerizable alumina-based ceramic core slurry. The ceramic core is then obtained through photopolymerizable 3D printing, debinding, and sintering. In this method, the medium and fine powders form the matrix, while the coarse powder fills the matrix, exhibiting a "non-skeleton" microstructure. This microstructure is beneficial for controlling the trade-off between high porosity and mechanical properties in photopolymerizable 3D printed alumina-based ceramic cores, thereby improving the overall performance of the ceramic core.

[0005] The mechanical properties of ceramic cores can be improved by grading the powder. However, there is a lack of good design methods for how to achieve the best particle size distribution in the ceramic slurry stage to produce ceramic core materials with dense powder packing, high performance, good dimensional accuracy and no cracks. Usually, the gradation is adjusted by continuously adjusting the particle size distribution, which is costly and inefficient. Summary of the Invention

[0006] To address the aforementioned technical problems, this invention provides a method for designing the gradation of photocurable ceramic core powder and a method for preparing the core. By deriving the optimal particle matching model, it guides the gradation between fused silica powder and zirconium silicate powder of different particle sizes, achieving close packing of silica powder of different particle sizes and viscosity control of ceramic slurry, thereby effectively controlling the printing accuracy and interlayer bonding strength of photocurable ceramic cores.

[0007] The technical objective of this invention is achieved through the following technical solution: A method for designing the gradation of ceramic core powder in photopolymer additive manufacturing based on the principle of the densest natural stacking of spherical polygonal particles includes: S1. Obtain the particle size distribution of the ceramic powder to be graded. Perform a particle size distribution test on the ceramic powder to be graded, and use the D50 measurement data as an approximation of the equivalent spherical diameter. S2. Calculate the total porosity of the system containing ceramic powders of different particle sizes using the Horsfield model. ; S3. Calculate the packing density, total surface energy E, and viscosity of the ceramic suspension slurry for a multi-component system containing ceramic powders of different particle sizes. ; S4. By minimizing the total surface energy of the system and the viscosity of the ceramic suspension slurry and maximizing the packing density of the system, the optimal gradation model of the ceramic powder is output according to the weighting method. Based on the process setting constraints, the particle size ratio of each ceramic powder is calculated. S5. Prepare ceramic slurry according to the ceramic powder particle size ratio obtained in step S4, and make ceramic core samples; S6. Perform performance testing and analysis on the ceramic core samples.

[0008] Further, in step S4: Optimal gradation model Represented as: In the formula: , and These are the weighting coefficients. For calculating the viscosity of ceramic suspension slurry, For the total surface area calculation model of particles, D For the system's packing density calculation model, For reference, total surface area For reference relative viscosity, D ref For reference bulk density.

[0009] Furthermore, the minimum viscosity of the ceramic suspension slurry is expressed as: In the formula: The viscosity is the matrix viscosity. This represents the particle volume fraction. k For Einstein's coefficients, This is a model for calculating the porosity of the system. Minimizing the total surface energy of the system can be expressed as: In the formula: w This refers to the types and quantities of ceramic powders with different particle sizes in the system. For the first i Solid content per unit volume of a type of ceramic powder For the first i The diameter of the ceramic powder particles. For the first i Volume fraction of ceramic powder in slurry i =1,2,3,..., w; Maximizing the system packing density is expressed as: In the formula A model for calculating the average density of ceramic powder. To fill the order mapping function, q This refers to the types and quantities of powder particles involved in the particle filling calculation. For the first Volume fraction of ceramic powder in slurry For the first The maximum solid volume fraction that a type of ceramic powder can achieve when stacked individually.

[0010] Furthermore, =0.5, =0.3, =0.2.

[0011] Furthermore, During calculation: In the formula: denoted as , where is the particle radius of the ceramic powder.

[0012] This invention also provides a method for preparing a photopolymer additive manufacturing ceramic core, the method comprising: Step 1: Place a 30μm diameter Spherical powder, with a diameter of 22μm Polygonal powder, 20μm in diameter Spherical powder, 5μm in diameter Spherical powder, 1μm in diameter Spherical powder and zirconium silicate polygonal powder with a diameter of 17μm were graded to obtain ceramic powder. The ceramic powder was mixed with DLP photosensitive resin, dipentaerythritol hexapropionate, wetting and dispersing agent and polypropylene glycol in proportion, and ball milled to obtain a dispersion slurry. Step 2: Vacuum the dispersion slurry to remove air bubbles. Step 3: Perform a viscosity test. Once the viscosity test meets the printing requirements, proceed with the raw preform printing. Step 4: Degreasing and sintering. Segmented heating sintering is adopted during sintering. After reaching each set temperature gradient, the temperature is held for a set time before heating to the next temperature gradient. Step 5: Immerse the ceramic core obtained after sintering in Step 4 into the strengthening liquid for full impregnation. After removing the strengthening liquid from the surface of the ceramic core, dry it to obtain the strengthened ceramic core.

[0013] Further, in step 1, a diameter of 30 μm The spherical powder has a volume fraction of 6.31 vol% and a diameter of 22 μm. The polygonal powder has a volume fraction of 30.62 vol% and a diameter of 20 μm. The spherical powder has a volume fraction of 1.87 vol% and a diameter of 5 μm. The spherical powder has a volume fraction of 10.20 vol% and a diameter of 1 μm. The volume fraction of spherical powder is 12.46 vol%, and the volume fraction of zirconium silicate polygonal powder with a diameter of 17 μm is 3.54 vol%.

[0014] Furthermore, the volume fraction of DLP photosensitive resin is 18.26 vol, the volume fraction of dipentaerythritol hexaacrylate is 3.08 vol, the volume fraction of wetting and dispersing agent is 6.49 vol, and the volume fraction of polypropylene glycol is 7.17 vol.

[0015] Furthermore, the reinforcing liquid is prepared by mixing epoxy resin, curing agent, diluent and 2,4,6-tris(dimethylaminomethyl)phenol in a mass ratio of 1:1:1:0.015.

[0016] Furthermore, during the segmented heating and sintering process in step 4: First, raise the temperature to 180℃ at a rate of 1℃ / min and then hold it at that temperature for 60min. Then, the temperature was increased sequentially to 268℃, 360℃, 515℃, and 600℃ at a rate of 0.6℃ / min, and held for 300min, 360min, 240min, and 240min respectively. Finally, the temperature was increased to 1210℃ at a rate of 0.8℃ / min and held for 240 minutes.

[0017] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. The design method of this invention can guide the gradation of different particle sizes of ceramic powder based on the optimal particle matching model, reduce trial and error costs, achieve efficient material iteration, greatly shorten the iteration cycle of advanced complex ceramic core structures, shorten the verification cycle of advanced aero-engines, reduce the R&D cost and mass production cost of turbine blade structures, and is conducive to the greening of intelligent manufacturing and reducing energy consumption.

[0018] 2. The ceramic powder particle size distribution obtained by the design method of the present invention, and the ceramic core obtained by the preparation method of the present invention, exhibit no crack initiation, good surface quality, low shrinkage, low porosity, and room temperature flexural strength and high temperature flexural strength that meet the requirements for use. Attached Figure Description

[0019] Figure 1 This is a schematic flowchart of the method for designing the gradation of ceramic core powder in photopolymer additive manufacturing based on the principle of the densest natural stacking of spherical polygonal particles, according to the present invention.

[0020] Figure 2 This is a temperature rise curve of degreasing and sintering of the ceramic core sample in this invention.

[0021] Figure 3 This is a comparison image of the ceramic core sample before and after sintering strengthening in this invention. Detailed Implementation

[0022] The technical solution of the present invention will be further described below with reference to specific embodiments: A method for designing the gradation of ceramic core powders for photopolymer additive manufacturing based on the principle of the densest natural stacking of spherical polygonal particles, such as... Figure 1 As shown, it includes: S1. Obtain the particle size distribution of the ceramic powder to be graded. Perform particle size distribution testing on the ceramic powder to be graded, and use the D50 measurement data as an approximation of the equivalent spherical diameter; for fused silica powders of different particle sizes ( The particle size distribution was measured using a laser particle size analyzer, including spherical powder with a diameter of 30 μm, polygonal powder with a diameter of 22 μm, spherical powder with a diameter of 20 μm, spherical powder with a diameter of 5 μm, and spherical powder with a diameter of 1 μm. For zirconium silicate powder, the laser particle size analyzer determined the particle size to be polygonal powder with a diameter of 17 μm. The parameters of the six powder sizes used to enhance the flexural strength of photocurable ceramic cores after sintering are shown in Table 1. S2. Calculate the total porosity of the system containing ceramic powders of different particle sizes using the Horsfield model. ; Based on the above measurement results, the spheres with the largest diameter (referred to as first-order spheres) are arranged in a close-packed configuration in space. This arrangement is either hexagonal close-packed or face-centered cubic. According to geometric principles, its initial porosity is... and A constant value: Based on Horsfield's dense packing theory, and following the order of pore size from largest to smallest, the subsequent levels of filled spheres are defined as follows: Diameter of secondary spheres (octahedral pores formed after the densest packing of primary spheres) The diameter of a first-order sphere The ratio satisfies the geometric constraints: Diameter of a third-order sphere (the tetrahedral pore formed after the densest packing of first-order spheres) The diameter of a first-order sphere The ratio satisfies the geometric constraints: The diameter ratio of higher-level spheres (smaller residual pores formed after filling the previous-level spheres) is calculated based on the specific pore geometry.

[0023] The total porosity of the system is calculated using the following iterative formula: In the formula: The total porosity of the system after n-stage filling. is the initial porosity, and n is the total number of stages of filling (n≥2). For the first The volume fraction of a sphere in a multi-level packing system needs to be determined based on the geometric relationship between the actual diameter of the sphere and the pore size, as well as the packing efficiency.

[0024] S3. Calculate the packing density D, total surface energy E, and viscosity of the ceramic suspension slurry for a multi-component system containing ceramic powders of different particle sizes. ; In the formula: The average density of the ceramic powder is given.

[0025] In the formula: The viscosity of the slurry. The viscosity is the matrix viscosity. This represents the particle volume fraction. The maximum stacking fraction is given by k, where k is the Einstein coefficient. ; In the formula: E is the total surface energy of the system. For surface energy, The total surface area of ​​the particles. Where the particle radius is; According to thermodynamic principles, a system has its lowest energy when it remains stable, and the total surface area of ​​particles per unit volume in the surface system is the lowest energy level. Minimum, that is To maintain a minimum solid content per unit volume of slurry, let the solid content per unit volume be... : Therefore, we obtain the first... i The solid content per unit volume of the ceramic powder is: In the formula: denoted as , where is the particle radius of the ceramic powder.

[0026] S4. Minimize the total porosity of the system by achieving the target. Total surface energy E of the system and viscosity of the ceramic suspension slurry The optimal gradation model of ceramic powder is output according to the weighting method, and the particle size ratio of each ceramic powder is calculated according to the process setting constraints. The minimum viscosity of the ceramic suspension slurry is expressed as: In the formula: The viscosity is the matrix viscosity. This represents the particle volume fraction. k For Einstein's coefficients, This is a model for calculating the porosity of the system. Minimizing the total surface energy of the system can be expressed as minimizing the total surface area. : In the formula: w This refers to the types and quantities of ceramic powders with different particle sizes in the system. For the first i Solid content per unit volume of a type of ceramic powder For the first i The diameter of the ceramic powder particles. For the first i Volume fraction of ceramic powder in slurry i=1,2,3,..., w; In this embodiment w =6, minimize total surface area : ; The maximum total packing density of the system is expressed as: In the formula: To fill the order mapping function, q This refers to the types and quantities of powder particles involved in the particle filling calculation. For the first Volume fraction of ceramic powder in slurry For the first The maximum solid volume fraction that a type of ceramic powder can achieve when stacked individually; For the calculation model of average density of ceramic particles, For the first The density of the ceramic powder For the first The volume of the ceramic powder; The core of the multi-level packing model is to fill the pores left by the previous level of particles with smaller particles. Therefore, only powders with a particle size significantly smaller than the skeletal particles of the previous level can enter the filling sequence. Particles with a particle size similar to or larger than the skeletal particles do not participate in filling but serve as part of the skeletal structure. In this embodiment, 30μm particles... Spherical powder as 22μm The shared framework of polygonal powder, 20μm The amount of spherical powder used is extremely small and is only used for process adjustment to improve cracking. Therefore, it does not participate in the filling sequence. The value of j is 1, 2, 3, 4, that is, q=4.

[0027] More specifically, =2, =6, =4, =5. Corresponding to 22μm Polygonal powder (containing 30μm) (spherical powder) Corresponding to 17μm For deformable powder, Corresponding to 5μm Spherical powder, Corresponding to 1μm Spherical powder.

[0028] The powder proportions are obtained by solving the following multi-objective optimization problem: st The multi-objective problem is transformed into a single-objective problem using a weighting method, resulting in the optimal gradation model. Represented as: In the formula: , and These are the weighting coefficients. For calculating the viscosity of ceramic suspension slurry, For the total surface area calculation model of particles, D For the system's packing density calculation model, For reference, total surface area For reference relative viscosity, D ref For reference bulk density. In this embodiment, the maximum viscosity allowed for printing by the photopolymerization printing equipment is used. The value is taken as 50 Pa·s, and the total surface area under the smallest particle size powder is used as... .

[0029] To achieve low shrinkage and low deformation after sintering of the photocurable ceramic core, the total solid content of the powder is controlled at 65% by volume. For the first i Volume fraction of ceramic powder in slurry ( i =1,2,3,4,5,6), the total solids content constraint must be met: In the formula: 0.65 indicates that the total volume of solid powder accounts for 65% of the total volume of slurry.

[0030] Set process constraint 1: 22μm polygonal powder, as the main basic particle, accounts for no less than 40% of the solid phase. ,but ≥0.26; Set process constraint 2: To improve the cracking resistance of photocurable ceramic cores after sintering, 20μm spherical powder should account for no more than 2% of the solid phase. ; Process constraint 3: To enhance the flexural strength of the ceramic core, and to ensure that zirconium silicate 17μm polygonal powder does not excessively affect the core shrinkage rate, its mass fraction in the entire system is 8%-10%. Then: ; Set process constraint 4: 5μm spherical powder and To enhance the flexural strength of the ceramic core, 1μm spherical powder must constitute at least 15% of the solid phase. ; Will and Substitute into the following formula: st The powder gradation ratio was obtained by solving the problem using Python, and the results are shown in Table 2.

[0031] S5. Prepare ceramic slurry according to the ceramic powder particle size ratio obtained in step S4, and make ceramic core samples; During preparation, according to the above powder ratio, 18.26 vol% of DLP photosensitive resin, 3.08 vol% of dipentaerythritol hexapropylene ester (DPHA), 6.49 vol% of wetting and dispersing agent (BYK-9076), and 7.17 vol% of polypropylene glycol (PPG400) were added. The slurry was highly dispersed by ball milling at 400 rpm for 10 hours using a planetary ball mill. After ball milling, the slurry was vacuumed multiple times until there were no air bubbles in the ceramic slurry. Then, the viscosity was tested, and the viscosity of the ceramic slurry at 25℃ was 25.65 Pa·s, which met the printing requirements. Then, exposure printing was performed through a DLP projection device with an exposure power of 120 uw / cm² and an exposure time of 1.8 s.

[0032] After printing, the residual resin on the surface of the ceramic core blank is cleaned, the support is removed, and it is placed in a sintering furnace for degreasing and sintering. During sintering, the dried silicon-based ceramic core is placed in a high-temperature sintering furnace and heated to 180℃ at a rate of 1℃ / min, and held for 60 min; then the temperature is increased to 268℃, 360℃, 515℃, and 600℃ respectively at a rate of 0.6℃ / min. After heating to 268℃, it is held for 300 min; after heating to 360℃, it is held for 360 min; after heating to 515℃, it is held for 240 min; after heating to 600℃, it is held for 240 min; then the temperature is increased to 1210℃ at a rate of 0.8℃ / min and held for 240 min. After cooling to room temperature in the furnace, the sintered ceramic core sample is taken out. The heating curve is shown below. Figure 2 As shown; The sintered ceramic core sample is then immersed in a strengthening solution. The strengthening solution is prepared by mixing epoxy resin, curing agent, diluent (PMA), and 2,4,6-tris(dimethylaminomethyl)phenol in a mass ratio of 1:1:1:0.015. After immersion, excess strengthening solution is removed from the surface, and the sample is dried at 110°C for 6 hours to obtain the ceramic core.

[0033] S6. Perform performance testing and analysis on the ceramic core samples.

[0034] Comparison of before sintering and after sintering strengthening, for example Figure 3 As shown, the reinforced ceramic core printing exhibited no crack initiation and good surface quality. After testing for shrinkage rate, water absorption rate, and room temperature / high temperature flexural strength, its performance met the requirements. The test results are shown in Table 3. This embodiment also provides a method for preparing a photopolymer additive manufacturing ceramic core, the method comprising: Step 1: Place a 30μm diameter Spherical powder, with a diameter of 22μm Polygonal powder, 20μm in diameter Spherical powder, 5μm in diameter Spherical powder, 1μm in diameter Ceramic powder was obtained by grading spherical powder and zirconium silicate polygonal powder with a diameter of 17μm. The ceramic powder was then mixed with DLP photosensitive resin, dipentaerythritol hexapropionate, wetting and dispersing agent (BYK9076), and polypropylene glycol in a certain proportion, and ball milled to obtain a dispersion slurry. 30μm in diameter The spherical powder has a volume fraction of 6.31 vol% and a diameter of 22 μm. The polygonal powder has a volume fraction of 30.62 vol% and a diameter of 20 μm. The spherical powder has a volume fraction of 1.87 vol% and a diameter of 5 μm. The spherical powder has a volume fraction of 10.20 vol% and a diameter of 1 μm. The volume fraction of spherical powder was 12.46 vol%, and the volume fraction of zirconium silicate polygonal powder with a diameter of 17 μm was 3.54 vol%. The volume fraction of DLP photosensitive resin is 18.26 vol, the volume fraction of dipentaerythritol hexaacrylate is 3.08 vol, the volume fraction of wetting and dispersing agent is 6.49 vol, and the volume fraction of polypropylene glycol is 7.17 vol.

[0035] Step 2: Vacuum the dispersion slurry to remove air bubbles. Step 3: Perform a viscosity test. Once the viscosity test meets the printing requirements, proceed with the raw preform printing. Step 4: Degreasing and sintering. Segmented heating sintering is adopted during sintering. After reaching each set temperature gradient, the temperature is held for a set time before heating to the next temperature gradient. The specific process is as follows: First, raise the temperature to 180℃ at a rate of 1℃ / min and then hold it at that temperature for 60min. Then, the temperature was increased sequentially to 268℃, 360℃, 515℃, and 600℃ at a rate of 0.6℃ / min, and held for 300min, 360min, 240min, and 240min respectively. Finally, the temperature was increased to 1210℃ at a rate of 0.8℃ / min and held for 240 minutes. After cooling to room temperature in the furnace, it was removed.

[0036] Step 5: Immerse the ceramic core obtained after sintering in Step 4 into the strengthening liquid for full impregnation. After removing the strengthening liquid from the surface of the ceramic core, dry it to obtain the strengthened ceramic core. The strengthening liquid is prepared by epoxy resin, curing agent, diluent and 2,4,6-tris(dimethylaminomethyl)phenol in a mass ratio of 1:1:1:0.015.

[0037] This embodiment is merely a further explanation of the present invention and is not intended to limit the present invention. Those skilled in the art can make non-inventive modifications to this embodiment as needed after reading this specification, but such modifications are protected by patent law as long as they are within the scope of the claims of the present invention.

Claims

1. A method for designing the gradation of ceramic core powder in photopolymer additive manufacturing based on the principle of the densest natural stacking of spherical polygonal particles, characterized in that, include: S1. Obtain the particle size distribution of the ceramic powder to be graded. Perform a particle size distribution test on the ceramic powder to be graded, and use the D50 measurement data as an approximation of the equivalent spherical diameter. S2. Calculate the total porosity of the system containing ceramic powders of different particle sizes using the Horsfield model; S3. Calculate the bulk density, total surface energy, and viscosity of the ceramic suspension slurry of the multi-component system containing ceramic powders of different particle sizes. S4. By minimizing the total surface energy of the system and the viscosity of the ceramic suspension slurry and maximizing the packing density of the system, the optimal gradation model of the ceramic powder is output according to the weighting method. Based on the process setting constraints, the particle size ratio of each ceramic powder is calculated. S5. Prepare ceramic slurry according to the ceramic powder particle size ratio obtained in step S4, and make ceramic core samples; S6. Perform performance testing and analysis on the ceramic core samples.

2. The method for designing the gradation of ceramic core powder in photopolymer additive manufacturing based on the principle of the densest natural stacking of spherical polygonal particles, as described in claim 1, is characterized in that... In step S4: Optimal gradation model Represented as: In the formula: , and These are the weighting coefficients. For calculating the viscosity of ceramic suspension slurry, For the total surface area calculation model of particles, D For the system's packing density calculation model, For reference, total surface area For reference relative viscosity, D ref For reference bulk density.

3. The method for designing the gradation of ceramic core powder in photopolymer additive manufacturing based on the principle of the densest natural stacking of spherical polygonal particles, as described in claim 2, is characterized in that... The minimum viscosity of the ceramic suspension slurry is expressed as: In the formula: The viscosity is the matrix viscosity. This represents the particle volume fraction. k For Einstein coefficients, This is a model for calculating the porosity of the system. Minimizing the total surface energy of the system can be expressed as: In the formula: w This refers to the types and quantities of ceramic powders with different particle sizes in the system. For the first i Solid content per unit volume of a type of ceramic powder For the first i The diameter of the ceramic powder particles. For the first i Volume fraction of ceramic powder in slurry i =1,2,3,..., w; Maximizing the system packing density is expressed as: In the formula: A model for calculating the average density of ceramic powder. Here, q represents the filling order mapping function, and q represents the type of powder particles involved in the particle filling calculation. For the first Volume fraction of ceramic powder in slurry For the first The maximum solid volume fraction that a type of ceramic powder can achieve when stacked individually.

4. The method for designing the gradation of ceramic core powder in photopolymer additive manufacturing based on the principle of the densest natural stacking of spherical polygonal particles, as described in claim 2, is characterized in that... =0.5, =0.3, =0.2。 5. The method for designing the gradation of ceramic core powder in photopolymer additive manufacturing based on the principle of the densest natural stacking of spherical polygonal particles, as described in claim 3, is characterized in that... The During calculation: In the formula: denoted as , where is the particle radius of the ceramic powder.

6. A method for preparing a ceramic core using photopolymer additive manufacturing, characterized in that, The method includes: Step 1: Place a 30μm diameter Spherical powder, with a diameter of 22μm Polygonal powder, 20μm in diameter Spherical powder, 5μm in diameter Spherical powder, 1μm in diameter Spherical powder and zirconium silicate polygonal powder with a diameter of 17μm were graded to obtain ceramic powder. The ceramic powder was mixed with DLP photosensitive resin, dipentaerythritol hexapropionate, wetting and dispersing agent and polypropylene glycol in proportion, and ball milled to obtain a dispersion slurry. Step 2: Vacuum the dispersion slurry to remove air bubbles. Step 3: Perform a viscosity test. Once the viscosity test meets the printing requirements, proceed with the raw preform printing. Step 4: Degreasing and sintering. Segmented heating sintering is adopted during sintering. After reaching each set temperature gradient, the temperature is held for a set time before heating to the next temperature gradient. Step 5: Immerse the ceramic core obtained after sintering in Step 4 into the strengthening liquid for full impregnation. After removing the strengthening liquid from the surface of the ceramic core, dry it to obtain the strengthened ceramic core.

7. The method for preparing a photocurable additive ceramic core according to claim 6, characterized in that, In step 1, the diameter is 30μm. The spherical powder has a volume fraction of 6.31 vol% and a diameter of 22 μm. The polygonal powder has a volume fraction of 30.62 vol% and a diameter of 20 μm. The spherical powder has a volume fraction of 1.87 vol% and a diameter of 5 μm. The spherical powder has a volume fraction of 10.20 vol% and a diameter of 1 μm. The volume fraction of spherical powder is 12.46 vol%, and the volume fraction of zirconium silicate polygonal powder with a diameter of 17 μm is 3.54 vol%.

8. The method for preparing a photocurable additive ceramic core according to claim 7, characterized in that, The DLP photosensitive resin has a volume fraction of 18.26 vol, the dipentaerythritol hexapropionate has a volume fraction of 3.08 vol, the wetting and dispersing agent has a volume fraction of 6.49 vol, and the polypropylene glycol has a volume fraction of 7.17 vol.

9. The method for designing the gradation of ceramic core powder in photopolymer additive manufacturing based on the principle of the densest natural stacking of spherical polygonal particles, as described in claim 6, is characterized in that... The reinforcing liquid is prepared by mixing epoxy resin, curing agent, diluent and 2,4,6-tris(dimethylaminomethyl)phenol in a mass ratio of 1:1:1:0.

015.

10. The method for preparing a photocurable additive ceramic core according to claim 8, characterized in that, During the segmented heating and sintering process in step 4: First, raise the temperature to 180℃ at a rate of 1℃ / min and then hold it at that temperature for 60min. Then, the temperature was increased sequentially to 268℃, 360℃, 515℃, and 600℃ at a rate of 0.6℃ / min, and held for 300min, 360min, 240min, and 240min respectively. Finally, the temperature was increased to 1210℃ at a rate of 0.8℃ / min and held for 240 minutes.

Citation Information

Patent Citations

  • Photocuring 3D printing alumina-based ceramic core and preparation method thereof

    CN114853450A